Review of the Provision of Job Placement Assistance and Related Employment Services to Members of the Reserve Components - Schaefer, Agnes Gereben (RAND Corporation, 2015)
This study identifies the current universe of federal employment programs and resources available to reserve component members, assesses the gaps and overlaps in those programs and resources, and develops recommendations for how the U.S. Department of Defense and the federal government as a whole can improve efforts to provide job placement assistance and related employment services to reserve component members.